0.36(6)+0.04x=0.12(18+x)

Simple and best practice solution for 0.36(6)+0.04x=0.12(18+x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.36(6)+0.04x=0.12(18+x) equation:


0.36(6) + 0.04x=0.12(18+x)

We simplify the equation to the form, which is simple to understand
0.36(6) + 0.04x=0.12(18+x)

Reorder the terms in parentheses
+(+2.16) + 0.04x=0.12*(18+x)

Remove unnecessary parentheses
+2.16 + 0.04x=0.12+*(+18+x+)

Reorder the terms in parentheses
+2.16 + 0.04x=+(+2.16 + 0.12x)

Remove unnecessary parentheses
+2.16 + 0.04x=+2.16 + 0.12x

We move all terms containing x to the left and all other terms to the right.
+ 0.04x-0.12x=+2.16-2.16

We simplify left and right side of the equation.
-0.08x=0

We divide both sides of the equation by -0.08 to get x.
x=-0

See similar equations:

| 4(6a-16)+2(2a+12)=4 | | 0.41x=8.2 | | -3(3y+v)+6(4v-4y)= | | 24-4(7-2t)=4(t-1) | | 950=25h+40 | | 1/2=-8 | | c=25h+40 | | -(2x+5)-9x= | | -x-2y=8 | | 3*32*3+u=(3*3*3-3*8)(2)+u | | 8(3x-6)=2(12x+4) | | -(4u-6)-u= | | 8x-3(3x+2)= | | 2x^2+22=0 | | 7(x-7)+16= | | 92=6(x-70)+50 | | 2x^4-x^3-x^2=0 | | x^2+y^2-4x-6y+4=0 | | 2y-2=6y+2 | | -2(-y-2)-x= | | 6x^2+7x-3=y | | .2+.2x=.4 | | 12x^2+82x-14=0 | | 3(1+d)+-5=3d+-2 | | 3x^2-35x-5=0 | | 6x-1=6x+12 | | 2yw+4y-yw-3y= | | -4w+1+w-6= | | kv-kv^2=q | | (6y+4)-(2+5y)=8 | | -20+X=51 | | 12x+3x-12=0 |

Equations solver categories